Does Wealthier Imply Healthier and Happier? Examining the Relationship Between Wealth, Health, and Happiness (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human Development and well being go way beyond per capita GDP but at the same time it would be incorrect to exclude per capita GDP from the list of its determinants. A cross country correlation between a) per capita GDP and life expectancy, b) per capita GDP and World Happiness Index is attempted separately to explore the linkages and patterns emerging. The cross country analysis of distinct time periods is also compared to bring out some general or secular trends if any. Some plausible explanations for the patterns observed are tendered along with the caveats that must be kept in mind while carrying out such an analysis.